Atrazina - aprovações de agrotóxicos no Brasil, seus efeitos ao meio ambiente e para os seres humanos - Fuziwara, Mayara Tiemi (Universidade Federal de São Carlos, 2023)
With the significant population growth in recent years and the recent global reach of 8 billion people, the lack of food for everyone has become a recurring discussion. In order to achieve higher yields in crops, the use of pesticides has become an increasingly intense practice, and in Brazil, the number of new registered products is breaking records, with 562 new patents in 2021 alone. The sale of pesticides is also high, with approximately 720,000 tons of volume in 2021, with herbicides standing out as responsible for more than half of the volume of active ingredients consumed. For this work, carried out in the form of a literature review, the active ingredient atrazine was chosen, and its effects on human beings were addressed, with its effect becoming inconclusive as there are still many differences between older and more recent studies. A strong residual presence was observed in the soil, damaging the yield of the next crops planted in the region, as well as causing effects on microorganisms and invertebrates that inhabit the area. In the case of water, a much greater complexity of effects was observed, with the persistence of the active ingredient in the environment harming the entire food chain of aquatic animals.
Atrazine - approvals of pesticides in Brazil, their effects on the environment and human beings
Keywords: Atrazina; Herbicida; Efeitos ambientais; Atrazine; Herbicide; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA